Students’ Perceptions and Satisfaction Analysis Towards Online Guidance and Counseling Services During Covid-19 Pandemic - Nina Alfa Rizkana; Sofia Farzanah Sulaeman; Venazmi Livia Buamona; Herdi Herdi; Tamima Rubama (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
The Covid-19 pandemic has brought about fundamental changes in providing school guidance and counseling services. The provision of services that were previously done offline, now it was changed to online. This study examines the descriptions of students' perceptions and level of satisfaction with online guidance and counseling services. The purposive sampling technique was done by surveying and sampling. A total of 246 respondents were obtained with the use of perception assessment as the instrument and CSQ-8 to measure the level of satisfaction. The results showed that students had a good perception of online Guidance and Counseling (BK) services and had a moderate or satisfactory level of satisfaction.